The Meaning of Being a Teacher in the Generation of Gen Z in the Phenomenological Approach - Rahmawati, Rahmawati; Rizal, Yon; Nurdin, Nurdin (FKIP Universitas Lampung, 2024)
The purpose of this study was to determine the meaning of being a teacher in the generation of Gen Z in the phenomenological approach and to determine the perspective of motivation related point of view to be a teacher in the generation of gen Z. this study uses a qualitative design using a phenomenological approach, namely researchers trying to enter the conceptual world of the subjects studied, namely gen z students of Economic Education Class of 2020. Data collection techniques include in-depth interviews and documentation. Based on the results of the study, the findings obtained 1) The Meaning of teachers according to Generation Z is that teachers are not smart teachers for themselves but for their students as well, 2) the most dominant encouragement to date is the parents, not only the support of parents of peers, the environment and social media also influence in determining the next steps. 3) rumors about a small salary, must PPG and compete with non FKIP, Teacher Platform. that this is not just a rumor but a serious problem that must be addressed.Keywords: Meaning of Being a Teacher, Generation ZDOI: http://dx.doi.org/10.23960/E3J/v7i1.72-77